2017
DOI: 10.1093/sleepj/zsx050.160
|View full text |Cite
|
Sign up to set email alerts
|

0161 Active and Passive Bedtime Social Technology Use Related to Daytime Sleepiness and Sleep

Abstract: Introduction:The caudal hypothalamus contains a key node of the ascending arousal system, with lesions causing more profound somnolence than can be accounted for by involvement of nearby hypothalamic orexin and histamine cell groups. Methods: We used chemogenetic manipulations and Cre-lox glutamate release disruption in anatomically-and genetically-targeted neuronal groups of the caudal hypothalamus and recorded EEG and EMG, with subsequent histological analysis of injection sites and terminal fields of transd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Passive use of social networking sites is an adverse factor for sleep disorders in adolescents. Passive use of social networking sites reduces adolescents' sleep quality (Bouwman, 2021), disrupts their sleep patterns (Mastin et al, 2017), causes sleep disorders (Polos et al, 2015), and hinders students' normal life and ability to study. After controlling both web browsing and iPad light levels, however, Bowler and Bourke (2019) demonstrated that passive social network use was related to the iPad light level instead of healthy sleep.…”
Section: Impact Of Passive Social Networking Site Use On Adolescents'...mentioning
confidence: 99%
“…Passive use of social networking sites is an adverse factor for sleep disorders in adolescents. Passive use of social networking sites reduces adolescents' sleep quality (Bouwman, 2021), disrupts their sleep patterns (Mastin et al, 2017), causes sleep disorders (Polos et al, 2015), and hinders students' normal life and ability to study. After controlling both web browsing and iPad light levels, however, Bowler and Bourke (2019) demonstrated that passive social network use was related to the iPad light level instead of healthy sleep.…”
Section: Impact Of Passive Social Networking Site Use On Adolescents'...mentioning
confidence: 99%
“…2 Other studies found that both "active" SM use (i.e., liking, commenting, or interacting with other users) and "passive" SM use (i.e., the possibility that SM notifications and disruptions could affect sleep in the absence of action) are related to disturbed sleep. 3 Because of the large amount of SM use among young adults, 4 the persistent associations between SM use and disturbed sleep, and evidence that certain aspects of SM use are related to disturbed sleep, it is important to work to identify possible points of intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of SM, it has been hypothesized that the stimulating nature of SM could contribute to sleep disturbance, regardless of valence. 3 If this hypothesis holds true, positive experiences offline and online could be linked to greater sleep disturbance. Previous research has found associations between negative experiences on SM and both depression 12 and social isolation, 13 suggesting that the ways users interact with others on SM and subsequently interpret those reactions may be related to health outcomes.…”
Section: Introductionmentioning
confidence: 99%